Kargo Kullanıcılarının Önem Verdikleri Faktörlerin, Kargo Firmaları Tarafından Başarım Düzeylerinin İncelenmesi / The Achievement Level of Factors which Cargo Users Care about by Cargo Companies - Çakmak, Ali Çağlar; Özkan, Bekir (Journal of History Culture and Art Research, 2017)
Abstract The service which is provided by courier companies that we often use in our daily life has a great importance for their customers. To deliver a received or sent cargo on time without having damage is one of the most effective factors that comprise this importance. From this point of view, the main purpose of this study is to determine the services that the customers set great care about and to find out to what extent can the courier companies fulfill these demands. For this purpose, in this study the evaluation of the companies by the customers are assessed by using importance-performance analysis. According to the obtained results, the factors which the customers set care the most are; “delivering the post without any deficiency”, “not to open” and “delivering to designated address”. The least important factors are; “to ask help while carrying the cargo”, “the physical conditions of the company” and “applying existing campaigns”. When we look at the courier companies, through the most preferred three companies: Yurtiçi Cargo, Aras Cargo and PTT Cargo, “PTT Cargo” has the highest performance average while “Yurtiçi Cargo” has the lowest. Öz Günlük hayatımızda sıklıkla kullandığımız kargo firmalarının verdikleri hizmet, bu hizmeti alan kullanıcıları için büyük önem arz etmektedir. Gönderilen veya alınan kargonun zamanında teslim edilmesi, herhangi bir hasar görmemesi de bu önemin oluşmasındaki en etkili unsurlardandır. Buradan hareketle bu çalışmanın ana amacı, kullanıcıların en çok önem verdikleri hizmetlerin belirlenmesi ve çalıştıkları kargo firmalarının bu hizmetleri ne ölçüde yerine getirebildiklerinin ortaya çıkarılmasıdır. Bu amaçla, bu çalışmada kullanıcıların kargo firmalarını değerlendirmeleri önem-başarım analizi kullanılarak ölçülmüştür. Elde edilen sonuçlara göre kullanıcıların en çok önem verdiği unsurlar; gönderinin eksiksiz teslimi, açılıp kurcalanmaması ve belirtilen adrese teslimidir. En az önem verdiği unsurlar ise; kargo taşınırken müşteriden yardım istenmesi, firmanın fiziksel koşulları ve mevcut kampanyaların uygulanmasıdır. Kargo firmalarına bakıldığında, en çok kullanılan üç kargo firmasında (Yurtiçi kargo, Aras kargo, PTT kargo) başarım ortalaması en yüksek PTT kargo iken, en düşük olan Yurtiçi kargodur.